Hadith #3506 - Sahih al-Bukhari - Amr bin 'Asim al-Kalabi عمرو بن عاصم الكلابي (Sahih al-Bukhari)
The Prophet (ﷺ) deputed me to read the Army of Dhat-as-Salasil. I came to him and said, “Who is the most beloved person to you?” He said, ” `Aisha.” I asked, “Among the men?” He said, “Her father.” I said, “Who then?” He said, “Then `Umar bin Al-Khattab.” He then named other men.
Grade: Sahih

Hadith #5762 - Sahih al-Bukhari - Amr bin 'Asim al-Kalabi عمرو بن عاصم الكلابي (Sahih al-Bukhari)
I heard the Prophet (ﷺ) saying openly not secretly, “The family of Abu so-and-so (i.e. Talib) are not among my protectors.” `Amr said that there was a blank space (1) in the Book of Muhammad bin Ja`far. He added, “My Protector is Allah and the righteous believing people.” `Amr bin Al-`As added: I heard the Prophet (ﷺ) saying, ‘But they (that family) have kinship (Rahm) with me and I will be good and dutiful to them. “
Grade: Sahih

Hadith #7071 - Sahih al-Bukhari - Amr bin 'Asim al-Kalabi عمرو بن عاصم الكلابي (Sahih al-Bukhari)
That he heard Allah’s Messenger (ﷺ) saying, “If a judge gives a verdict according to the best of his knowledge and his verdict is correct (i.e. agrees with Allah and His Apostle’s verdict) he will receive a double reward, and if he gives a verdict according to the best of his knowledge and his verdict is wrong, (i.e. against that of Allah and His Apostle) even then he will get a reward .”
Grade: Sahih